Antibacterial and mildew-proof degradable carton packaging material and preparation method thereof
Patent Information
- Application Number
- CN202611321887.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]基于上述情况,本发明需要解决的技术问题是如何在保持纸盒包装材料可降解性并采用温和加工条件的基础上,构建兼具抗菌和防霉功能的多层结构,同时解决外侧防霉层对内侧接触型抗菌位点产生覆盖和屏蔽的问题,使两类功能层能够在同一纸板材料中稳定共存并分别发挥作用
[0024]1、所形成的五层抗菌复合层以水溶性2-羟丙基三甲基氯化铵壳聚糖作为首层和最外层,并利用羧甲基纤维素钠层进行间隔和固定。该层状结构能够减少抗菌成分在使用过程中的迁移和流失,同时使最外层保留较多可与细菌接触的季铵阳离子位点。细菌细胞表面通常带有负电荷,当细菌附着于该复合层时,季铵阳离子可与细菌细胞表面产生静电吸附,扰乱细胞包膜原有的电荷平衡,增加细胞膜通透性,进而引起胞内离子和小分子物质外泄,抑制细菌的生长与繁殖。羧甲基纤维素钠位于相邻阳离子层之间,有利于提高涂层在纸板表面的结合稳定性;最外层重新采用2-羟丙基三甲基氯化铵壳聚糖,则能够避免抗菌活性位点被内部聚阴离子材料过度遮蔽,使纸板表面保持接触型抗菌能力。
Smart Images

Figure CN122899088A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of green packaging materials technology, belonging to patent classification number B65D65 / 46, specifically to an antibacterial, mildew-resistant, and biodegradable paper box packaging material and its preparation method. Background Technology
[0002] Paperboard packaging materials are lightweight, easy to process, easy to print, and recyclable, making them widely used in food, daily necessities, and agricultural product packaging. Paperboard made from plant fibers such as sugarcane bagasse pulp and bamboo pulp also features renewable raw materials and biodegradability in the natural environment, reducing the environmental burden caused by traditional plastic packaging. However, plant fiber paperboard contains a large number of hydrophilic groups and pores, making it prone to absorbing moisture from the environment during storage and transportation. When the packaging environment has high temperature and humidity, bacteria and mold easily adhere to the surface of the paperboard, potentially contaminating the packaged goods and causing problems such as mold spots, odors, and reduced fiber strength. This limits the application of biodegradable paperboard in food and other packaging fields with high hygiene requirements.
[0003] To improve the microbial protection performance of cardboard boxes, functional coatings containing antibacterial or antifungal components can be applied to the cardboard surface. However, bacteria and fungi differ in cell structure, growth conditions, and sensitivity to active substances, making it difficult for a single functional component to simultaneously achieve stable antibacterial and antifungal effects. Some antibacterial substances primarily exert their effects through contact with bacterial cell membranes via surface charge, requiring a sufficient number of accessible active sites. While some plant-derived antifungal substances exhibit good antifungal activity, they suffer from poor dispersibility in water, rapid evaporation, and susceptibility to loss during processing and storage. Simply mixing different functional substances directly can lead to flocculation, encapsulation, or mutual masking of active sites, reducing the stability of the coating solution and the final protective effect.
[0004] When antibacterial and antifungal layers are sequentially applied to the surface of cardboard, a significant interlayer interference problem arises. During film formation and cross-linking, the outer continuous antifungal film layer tends to cover the surface of the inner antibacterial layer and form interfacial associations with its charged groups, reducing the number of positively charged active sites that could directly contact bacteria. While this fixes and slows the release of the antifungal components, the contact bactericidal effect of the inner antibacterial layer may be weakened. Compensating for this by increasing the amount of antibacterial components not only increases manufacturing costs but may also affect coating uniformity, cardboard surface properties, and the biodegradability of the material.
[0005] Furthermore, biodegradable cardboard is not suitable for prolonged exposure to excessively high processing temperatures, and plant-derived volatile antifungal substances and protein-based active substances may be lost or deactivated due to heat. Therefore, the preparation of functional coatings requires the use of water-based, low-temperature, and easily achievable processing conditions, while avoiding the use of expensive or industrially unavailable raw materials.
[0006] Based on the above, the technical problem that this invention needs to solve is how to construct a multi-layer structure with both antibacterial and anti-mildew functions while maintaining the biodegradability of the cardboard packaging material and using mild processing conditions, and at the same time solve the problem of the outer anti-mildew layer covering and shielding the inner contact-type antibacterial sites, so that the two types of functional layers can coexist stably in the same cardboard material and play their respective roles. Summary of the Invention
[0007] The purpose of this invention is to provide an antibacterial, mildew-resistant, and biodegradable paper box packaging material and its preparation method, so as to solve the technical problems mentioned in the background art.
[0008] To achieve the above objectives, the present invention provides the following technical solution:
[0009] A method for preparing an antibacterial, mildew-resistant, and biodegradable paper box packaging material includes the following steps:
[0010] (1) Provide cellulose paperboard;
[0011] (2) On at least one side surface of the cellulose paperboard, water-soluble 2-hydroxypropyltrimethylammonium chloride chitosan aqueous solution and carboxymethyl cellulose sodium aqueous solution are prepared separately and coated layer by layer, and each layer is dried after coating to form a five-layer antibacterial composite layer consisting of a 2-hydroxypropyltrimethylammonium chloride chitosan layer, a carboxymethyl cellulose sodium layer, a 2-hydroxypropyltrimethylammonium chloride chitosan layer, a carboxymethyl cellulose sodium layer and a 2-hydroxypropyltrimethylammonium chloride chitosan layer from the cellulose paperboard outwards;
[0012] (3) The inclusion complex formed by β-cyclodextrin and thymol is dispersed in an aqueous coating system containing sodium alginate and calcium carbonate. Finally, gluconate-δ-lactone is added, and the resulting coating slurry is coated on the five-layer antibacterial composite layer before gelation is completed, so that the calcium ions released by calcium carbonate crosslink sodium alginate in situ, and an anti-mildew layer is formed after gelation and drying.
[0013] (4) After the anti-mildew layer has completed gelation, drying and cooling, a mixed aqueous solution containing ε-poly-L-lysine and lysozyme is applied to the surface of the anti-mildew layer away from the cellulose paperboard and dried to obtain the antibacterial and anti-mildew biodegradable paper box packaging material.
[0014] Preferably, the method for preparing the cellulose paperboard is as follows: 75-90 parts of bleached bagasse pulp and 10-25 parts of bamboo pulp are mixed, totaling 100 parts, based on a total oven-dry pulp mass of 100 parts; water is added to prepare a fiber pulp with a mass concentration of 1.0%-2.0%, and the pulp is beaten to 35-45°SR and then formed into a wet paper sheet; the wet paper sheet is pressed at 0.3-0.6 MPa for 3-8 minutes and dried at 80-95°C to a moisture content of 6%-9%, yielding a basis weight of 300-450 g / m³. 2 Cellulose paperboard.
[0015] Preferably, before forming the five-layer antibacterial composite layer, the cellulose paperboard is surface-sized. The surface sizing includes: preparing an aqueous dispersion of oxidized corn starch with a mass concentration of 4% to 6%, gelatinizing it at 85 to 95°C for 15 to 25 minutes, and applying it at a concentration of 40 to 60 g / m³. 2 A wet coating is applied to the surface of the cellulose paperboard and dried at 80-90°C to form an oxidized corn starch sizing layer; the five-layer antibacterial composite layer is formed on the oxidized corn starch sizing layer.
[0016] Preferably, the 2-hydroxypropyltrimethylammonium chloride chitosan has a quaternary ammonium group substitution degree of 0.70–0.90 and a number-average molecular weight of 5.0 × 10⁻⁶. 4 ~1.0×10 5 g / mol; the degree of substitution of the sodium carboxymethyl cellulose is 0.70–0.90; the mass concentration of the 2-hydroxypropyltrimethylammonium chloride chitosan aqueous solution is 0.8%–1.2%, the mass concentration of the sodium carboxymethyl cellulose aqueous solution is 0.4%–0.6%, and the pH of the two aqueous solutions is 5.8–6.2; the wet coating amount of each layer of 2-hydroxypropyltrimethylammonium chloride chitosan is 15–25 g / m². 2 The wet coating weight of each layer of sodium carboxymethyl cellulose is 18–28 g / m². 2 After each layer is coated, allow it to stand for 2–5 minutes, then remove excess liquid from the surface using an air knife. Dry each layer except the outermost layer at 40–50°C for 3–6 minutes, and dry the outermost layer at 45–55°C for 15–25 minutes. The total dry coating weight of the five antibacterial composite layers is 0.5–1.2 g / m². 2 .
[0017] Preferably, the inclusion complex is prepared as follows: β-cyclodextrin is dissolved in water at 50–60°C to prepare a β-cyclodextrin aqueous solution with a mass concentration of 4%–6%; thymol is dissolved in ethanol with a volume fraction of 95% to prepare a thymol ethanol solution with a mass concentration of 5%–10%; the thymol ethanol solution is added to the β-cyclodextrin aqueous solution within 10–20 min according to a molar ratio of β-cyclodextrin to thymol of 1:0.95–1.05, so that the volume fraction of ethanol in the resulting mixture is 8%–12%; the mixture is stirred at 50–60°C for 3–5 h in a reaction vessel equipped with a reflux condenser, then cooled to 2–8°C and allowed to stand for 8–16 h, filtered, and the resulting solid is washed with an ethanol aqueous solution with a volume fraction of 10% at a temperature of 2–8°C, and then vacuum dried at 35–40°C to obtain an inclusion complex with a particle size D90 of no more than 30 μm.
[0018] Preferably, based on the total mass of the coating slurry obtained after adding glucono-δ-lactone, the mass fraction of sodium alginate in the coating slurry is 1.3% to 1.7%, the mass fraction of the inclusion complex is 3.5% to 4.5%, the amount of glycerol added is 15% to 25% of the mass of sodium alginate, and the amount of calcium carbonate added is 5% to 8% of the mass of sodium alginate; the coating slurry is prepared by mixing and dispersing sodium alginate aqueous solution, glycerol, the inclusion complex and calcium carbonate and degassing, and finally adding glucono-δ-lactone aqueous solution.
[0019] Preferably, the molar ratio of gluconate-δ-lactone to calcium carbonate is 2.0–2.2:1; calculated based on the complete release of calcium ions from calcium carbonate, the molar ratio of calcium ions to carboxylate ions in sodium alginate is 0.10–0.16:1; after adding the gluconate-δ-lactone aqueous solution, mix for 20–40 seconds, and then add the solution at a concentration of 25–35 g / m³ within 5 minutes. 2 After applying the wet coating, let it stand at 25-30℃ for 10-20 minutes, and then dry it at 35-45℃ for 20-40 minutes.
[0020] Preferably, the ε-poly-L-lysine is ε-poly-L-lysine hydrochloride, and the lysozyme is egg white lysozyme; the mixed aqueous solution uses deionized water as a solvent, wherein the mass concentration of ε-poly-L-lysine hydrochloride is 0.15%–0.25%, the mass concentration of lysozyme is 0.25%–0.40%, the mass ratio of ε-poly-L-lysine hydrochloride to lysozyme is 0.45–0.75:1, the pH of the mixed aqueous solution is 5.8–6.2, and it does not contain phosphate buffer or citrate buffer.
[0021] Preferably, after cooling the anti-mildew layer to no higher than 35°C, apply it at a rate of 15–25 g / m³. 2The mixed aqueous solution is sprayed with a wet spray amount, allowed to stand for 5-10 minutes, and then dried at 30-35°C to achieve a total dry loading of 0.07-0.12 g / m³ for ε-poly-L-lysine hydrochloride and lysozyme. 2 .
[0022] An antibacterial, mildew-resistant, and biodegradable paper box packaging material is prepared by the method described above.
[0023] Compared with the prior art, the beneficial effects of the present invention are:
[0024] 1. The formed five-layer antibacterial composite layer uses water-soluble 2-hydroxypropyltrimethylammonium chloride chitosan as the first and outermost layers, and is separated and fixed by sodium carboxymethyl cellulose layers. This layered structure can reduce the migration and loss of antibacterial components during use, while allowing the outermost layer to retain more quaternary ammonium cation sites that can contact bacteria. Bacterial cell surfaces are usually negatively charged. When bacteria attach to this composite layer, quaternary ammonium cations can electrostatically adsorb onto the bacterial cell surface, disrupting the original charge balance of the cell membrane, increasing cell membrane permeability, and thus causing leakage of intracellular ions and small molecules, inhibiting bacterial growth and reproduction. Sodium carboxymethyl cellulose is located between adjacent cation layers, which helps to improve the bonding stability of the coating on the paperboard surface; the outermost layer uses 2-hydroxypropyltrimethylammonium chloride chitosan again, which can prevent the antibacterial active sites from being excessively blocked by the internal polyanionic material, so that the paperboard surface maintains contact antibacterial capability.
[0025] 2. The β-cyclodextrin in the anti-mold layer has hydrophobic cavities that can encapsulate thymol, thereby improving the uniformity of thymol dispersion in the aqueous coating system and reducing its volatilization loss during mixing, coating, and drying. The encapsulated thymol is no longer concentrated in a large free state but is gradually released from the β-cyclodextrin cavities as external moisture and inclusion balance change, which helps prolong the anti-mold effect time. The calcium cross-linking network formed by sodium alginate can uniformly fix the inclusion complex on the cardboard surface, reducing particle shedding and local aggregation, and providing continuous diffusion channels for thymol. The released thymol can enter the lipid region of the mold cell membrane through its hydrophobic structure, altering the integrity and permeability of the cell membrane, interfering with intracellular and extracellular ion balance and normal metabolism, thereby inhibiting mold spore germination and hyphal growth. The entire anti-mold layer is prepared using aqueous, low-temperature conditions, which also reduces the volatilization of thymol due to heat, balancing the stability of the anti-mold components and the processing adaptability of the cardboard substrate.
[0026] 3. After a continuous alginate antifungal layer covers the outside of the antibacterial composite layer, it physically and charge-shields the accessible positive potential sites of the inner 2-hydroxypropyltrimethylammonium chloride chitosan, making it difficult for bacteria to directly contact the original antibacterial surface, thus reducing the contact antibacterial effect. To solve this problem, after the antifungal layer has been gelled, dried, and cooled, ε-poly-L-lysine and lysozyme are co-loaded onto the outermost surface of the material. This arrangement does not remove the shielding effect of the antifungal layer on the inner antibacterial sites, but rather reconstructs an antibacterial interface on the outside of the antifungal layer that can directly contact bacteria, thereby compensating for the performance loss caused by the covering of the original antibacterial sites. Simultaneously, adding the two active ingredients after the gelation and main drying processes avoids them from being encapsulated in the uncured sodium alginate system and also reduces the impact of acidification, cross-linking, and high-temperature treatment on lysozyme activity. The ε-poly-L-lysine molecular chain contains multiple protonable amino groups, which carry a high density of positive charges under the weakly acidic conditions used. Lysozyme first adsorbs onto the negatively charged bacterial cell surface, weakening the electrostatic stability between adjacent components of the cell membrane, thus loosening the arrangement of the cell membrane or outer membrane and increasing permeability. For Gram-negative bacteria with an outer membrane barrier, this effect reduces the barrier of the outer membrane to macromolecular enzymes, making it easier for lysozyme to access the peptidoglycan layer located inside the outer membrane. Lysozyme then hydrolyzes the β-1,4-glycosidic bonds between N-acetylmuramic acid and N-acetylglucosamine in peptidoglycan, thinning or creating defects in the cell wall skeleton that supports cell morphology. With decreased cell wall strength, the increased membrane permeability and intracellular leakage caused by ε-poly-L-lysine become more pronounced, making it more difficult for bacteria to maintain normal osmotic pressure. For Gram-positive bacteria with directly exposed peptidoglycan layers, lysozyme first weakens the mechanical support of the cell wall, and then ε-poly-L-lysine further acts on the cell membrane, which has lost sufficient protection. For bacteria with strong outer membrane barriers, ε-poly-L-lysine first increases membrane permeability, creating conditions for lysozyme to approach the peptidoglycan. The two active substances thus form a continuous pathway of action: "increasing membrane permeability—exposing cell wall action sites—disrupting the peptidoglycan backbone—exacerbating membrane damage and leakage of contents." This action is not simply about increasing the dosage of the same antibacterial ingredient, but rather utilizes the synergistic effect of two different mechanisms—membrane interference and cell wall enzymatic hydrolysis—to simultaneously enable the outermost surface to have both cationic contact and enzymatic cell wall disruption, thereby more specifically compensating for the decrease in antibacterial ability caused by the antifungal layer covering. Attached Figure Description
[0027] Figure 1 This is a low-magnification SEM image of the antibacterial, mildew-resistant, and biodegradable paper box packaging material prepared in Example 1 of the present invention.
[0028] Figure 2 This is a high-magnification SEM image of the antibacterial, mildew-resistant, and biodegradable paper box packaging material prepared in Example 1 of the present invention. Detailed Implementation
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] The following examples all use 1.000m 2 The effective coating area on one side of the paperboard is used as the benchmark. Except for the volume fraction of ethanol, all percentages are mass percentages; pulp usage is based on oven-dry weight, and polymer and active ingredient usage is based on dry basis or active ingredient. Wet coating weight is the net increase in moisture content per unit area of the paperboard after air knife treatment or spraying, controlled by weighing before and after coating. pH is measured at 25℃ and adjusted using 0.10 mol / L hydrochloric acid aqueous solution or 0.10 mol / L sodium hydroxide aqueous solution, and then replenished with deionized water to the specified total mass after adjustment.
[0031] 2-Hydroxypropyltrimethylammonium chloride chitosan is abbreviated as HACC, sodium carboxymethyl cellulose is abbreviated as CMC-Na, and glucono-δ-lactone is abbreviated as GDL. The molar masses of β-cyclodextrin, thymol, GDL, and calcium carbonate are calculated as 1134.98 g / mol, 150.22 g / mol, 178.14 g / mol, and 100.09 g / mol, respectively; the carboxylate equivalent of sodium alginate is calculated as 198.11 g / mol. The measured density of 95% ethanol at 20°C is 0.805 g / mL. The labeled enzyme activity of the egg white lysozyme used is not less than 20000 U / mg.
[0032] Example 1
[0033] A method for preparing an antibacterial, mildew-resistant, and biodegradable paper box packaging material includes the following steps:
[0034] (1) Preparation of cellulose paperboard and sizing layer
[0035] 750,000 g of bleached bagasse pulp and 250,000 g of bamboo pulp were added to 99,000,000 g of deionized water to prepare 100,000,000 g of fiber pulp with a mass concentration of 1.0%. The pulp was beaten to 35°SR and then formed into paperboard. The resulting wet paperboard was pressed at 0.30 MPa for 3 minutes and dried at 80°C to a moisture content of 9.0%, with a basis weight controlled at 300 g / m². 2 Cut 1.000m 2 The cardboard is used for subsequent coating.
[0036] Add 4,000g of oxidized corn starch to 96,000g of deionized water and gelatinize at 85°C for 15 minutes with stirring. After cooling, add more deionized water to restore the total mass of the sizing solution to 100,000g. Apply 40,000g of the sizing solution to one side of the cardboard intended to be the inner surface of the carton and dry at 80°C for 10 minutes.
[0037] (2) Preparation of the five-layer antibacterial composite layer
[0038] 0.800 g of HACC was added to 80.000 g of deionized water. The HACC had a quaternary ammonium group substitution degree of 0.70 and a number-average molecular weight of 5.0 × 10⁻⁶. 4 g / mol; stir at 25℃ for 60 min, adjust pH to 5.8, and then make up to 100.000 g with deionized water to obtain a HACC aqueous solution with a mass concentration of 0.8%.
[0039] Add 0.400g of CMC-Na to 80.000g of deionized water, wherein the degree of substitution of CMC-Na is 0.70; stir at 25℃ for 120min, adjust the pH to 5.8, and then make up to 100.000g with deionized water to obtain a CMC-Na aqueous solution with a mass concentration of 0.4%.
[0040] The coating is applied layer by layer in the following order: HACC layer, CMC-Na layer, HACC layer, CMC-Na layer, and HACC layer again. The net wet coating weight of each HACC layer is 15,000 g / m². 2 The net wet coating weight of each CMC-Na layer is 18.000 g / m². 2 After each layer is coated, it is allowed to stand for 2 minutes, and the surface liquid is removed with an air knife; the first four layers are dried at 40℃ for 3 minutes each, and the outermost layer is dried at 45℃ for 15 minutes. Based on the net wet coating weight and solution concentration, the total dry coating weight of the five antibacterial composite layers is 0.504 g / m². 2 .
[0041] (3) Preparation of β-cyclodextrin / thymol inclusion complex
[0042] 22.6996 g of anhydrous β-cyclodextrin was added to 544.7904 g of deionized water and stirred at 50 °C to dissolve, yielding a 4.0% (w / w) β-cyclodextrin aqueous solution. 2.8542 g of thymol was dissolved in 54.2294 g of 95% (v / v) ethanol to obtain a 5.0% (w / w) thymol ethanol solution; the molar ratio of β-cyclodextrin to thymol was 1:0.95.
[0043] Under stirring at 50°C, the thymol ethanol solution was added to the β-cyclodextrin aqueous solution within 10 min. The mixture was then transferred to a reaction vessel equipped with a reflux condenser, and the volume was adjusted to 800.0 mL with deionized water to achieve an ethanol volume fraction of 8.0%. The mixture was stirred at 50°C for 3 h, then cooled to 2°C and allowed to stand for 8 h.
[0044] 4.21 mL of 95% ethanol was diluted to 40.0 mL with deionized water at 2 °C to prepare a 10% washing solution. The reaction solution was filtered, and the resulting solid was washed twice with 40.0 mL of the washing solution. The solid was then vacuum dried to constant weight at an absolute pressure not exceeding 20 kPa and 35 °C. The solid was then subjected to air jet milling and fractionation, and inclusion complexes with a particle size D90 not greater than 30 μm were collected.
[0045] (4) Preparation of the anti-mildew layer
[0046] Slowly add 1.3000g of sodium alginate to 92.5786g of deionized water and stir at 25℃ and 600r / min for 60min. Then add 0.1950g of glycerol, 3.5000g of the above inclusion complex and 0.0663g of calcium carbonate in sequence, disperse at 800r / min for 10min, and then degas for 5min under an absolute pressure not exceeding 20kPa.
[0047] 0.2360 g of GDL was dissolved in 2.1241 g of deionized water to obtain 2.3601 g of a 10.0% GDL aqueous solution. This GDL aqueous solution was then added to the above dispersion system and mixed for 20 seconds to obtain 100.000 g of anti-mildew coating slurry. The molar ratio of GDL to calcium carbonate was 2.00:1, and the molar ratio of calcium ions to sodium alginate carboxylate ions was 0.101:1.
[0048] Within 2 minutes of adding the GDL aqueous solution, apply the anti-mildew coating slurry at a rate of 25,000 g / m³. 2 The net wet coating amount is applied to the surface of the five-layer antibacterial composite layer, left to stand at 25℃ for 10 minutes, then dried at 35℃ for 20 minutes, and cooled to 25℃.
[0049] (5) Preparation of surface active layer
[0050] Add 0.1500 g of ε-poly-L-lysine hydrochloride and 0.3333 g of egg white lysozyme to 80.000 g of deionized water, stir gently at a temperature not exceeding 25°C, adjust the pH to 5.8, and then bring the total volume to 100.000 g with deionized water. No phosphate buffer or citrate buffer is added to the resulting aqueous solution. The mass ratio of ε-poly-L-lysine hydrochloride to lysozyme is 0.45:1.
[0051] The mixed aqueous solution was prepared at a concentration of 15,000 g / m³. 2 The net wet coating amount is sprayed onto the surface of the anti-mildew layer, left to stand for 5 minutes, and then dried at 30℃ for 60 minutes. Based on the coating amount and solution concentration, the total dry loading of ε-poly-L-lysine hydrochloride and lysozyme is 0.0725 g / m³. 2 The obtained material was equilibrated for 24 hours at 23±2℃ and 50±5% relative humidity.
[0052] Example 2
[0053] A method for preparing an antibacterial, mildew-resistant, and biodegradable paper box packaging material includes the following steps:
[0054] (1) Preparation of cellulose paperboard and sizing layer
[0055] 825,000 g of bleached bagasse pulp and 175,000 g of bamboo pulp were added to 65,666.700 g of deionized water to prepare 66,666.700 g of fiber pulp with a mass concentration of 1.5%. The pulp was beaten to 40°SR and then formed into paperboard. The resulting wet paperboard was pressed at 0.45 MPa for 5.5 min and dried at 88°C to a moisture content of 7.5%, with a basis weight controlled at 375 g / m². 2 Cut 1.000m 2 The cardboard is used for subsequent coating.
[0056] Add 5,000g of oxidized corn starch to 95,000g of deionized water and gelatinize at 90℃ for 20min under stirring. After cooling, add more deionized water to restore the total mass of the sizing solution to 100,000g. Apply 50,000g of the sizing solution to one side of the cardboard intended to be the inner surface of the carton and dry at 85℃ for 15min.
[0057] (2) Preparation of the five-layer antibacterial composite layer
[0058] 1.000g of HACC was added to 80.000g of deionized water. The HACC had a quaternary ammonium group substitution degree of 0.80 and a number-average molecular weight of 7.5 × 10⁻⁶. 4 g / mol; stir at 25℃ for 60 min, adjust pH to 6.0, and then make up to 100.000 g with deionized water to obtain a 1.0% HACC aqueous solution.
[0059] Add 0.500g of CMC-Na to 80.000g of deionized water, wherein the degree of substitution of CMC-Na is 0.80; stir at 25℃ for 120min, adjust the pH to 6.0, and then make up to 100.000g with deionized water to obtain a CMC-Na aqueous solution with a mass concentration of 0.5%.
[0060] The coating is applied layer by layer in the following order: HACC layer, CMC-Na layer, HACC layer, CMC-Na layer, and HACC layer again. The net wet coating weight of each HACC layer is 20,000 g / m². 2 The net wet coating weight of each CMC-Na layer is 28.000 g / m². 2 After each layer is applied, it is allowed to stand for 3.5 minutes, and the surface liquid is removed with an air knife. The first four layers are dried at 45℃ for 4.5 minutes each, and the outermost layer is dried at 50℃ for 20 minutes. Based on the net wet coating weight and solution concentration, the total dry coating weight of the five antibacterial composite layers is 0.880 g / m². 2 .
[0061] (3) Preparation of β-cyclodextrin / thymol inclusion complex
[0062] 22.6996 g of anhydrous β-cyclodextrin was added to 431.2924 g of deionized water and stirred at 55 °C to dissolve, yielding a 5.0% (w / w) β-cyclodextrin aqueous solution. 3.0044 g of thymol was dissolved in 37.0543 g of 95% (v / v) ethanol to obtain a 7.5% (w / w) thymol ethanol solution; the molar ratio of β-cyclodextrin to thymol was 1:1.00.
[0063] Under stirring at 55°C, the thymol ethanol solution was added to the β-cyclodextrin aqueous solution over 15 min, followed by 17.13 mL of 95% ethanol. The volume was then brought to a final volume of 600.0 mL with deionized water to achieve an ethanol volume fraction of 10.0%. The mixture was stirred at 55°C for 4 h in a reaction vessel equipped with a reflux condenser, then cooled to 5°C and allowed to stand for 12 h.
[0064] Prepare a 10% washing solution by diluting 5.26 mL of 95% ethanol to 50.0 mL with deionized water at 5 °C. Filter the reaction solution and wash the resulting solid twice with 50.0 mL of the washing solution. Vacuum dry the solid to constant weight under a pressure not exceeding 20 kPa and at 38 °C. Then, pulverize and classify the solid by air jet milling, collecting inclusion complexes with a particle size D90 not greater than 30 μm.
[0065] (4) Preparation of the anti-mildew layer
[0066] Slowly add 1.5000g sodium alginate to 90.4583g deionized water and stir at 25℃ and 600r / min for 60min. Then add 0.3000g glycerol, 4.0000g of the above inclusion complex and 0.0975g calcium carbonate in sequence, disperse at 800r / min for 10min, and then degas for 5min under an absolute pressure not exceeding 20kPa.
[0067] 0.3644 g of GDL was dissolved in 3.2798 g of deionized water to obtain 3.6442 g of a 10.0% GDL aqueous solution. This GDL aqueous solution was then added to the above dispersion system and mixed for 30 seconds to obtain 100.000 g of anti-mildew coating slurry. The molar ratio of GDL to calcium carbonate was 2.10:1, and the molar ratio of calcium ions to sodium alginate carboxylate ions was 0.129:1.
[0068] Within 3 minutes of adding the GDL aqueous solution, apply the anti-mildew coating slurry at a rate of 30,000 g / m³. 2 The net wet coating amount is applied to the surface of the five-layer antibacterial composite layer, left to stand at 28℃ for 15 minutes, then dried at 40℃ for 30 minutes, and cooled to 30℃.
[0069] (5) Preparation of surface active layer
[0070] Add 0.1875 g of ε-poly-L-lysine hydrochloride and 0.2500 g of egg white lysozyme to 80.000 g of deionized water, stir gently at a temperature not exceeding 25°C, adjust the pH to 6.0, and then bring the total volume to 100.000 g with deionized water. No phosphate buffer or citrate buffer is added to the resulting aqueous solution. The mass ratio of ε-poly-L-lysine hydrochloride to lysozyme is 0.75:1.
[0071] The mixed aqueous solution was prepared at 25.000 g / m³. 2 The net wet coating amount was sprayed onto the surface of the anti-mildew layer, allowed to stand for 7.5 minutes, and then dried at 33℃ for 45 minutes. Based on the coating amount and solution concentration, the total dry loading of ε-poly-L-lysine hydrochloride and lysozyme was 0.1094 g / m³. 2 The obtained material was equilibrated for 24 hours at 23±2℃ and 50±5% relative humidity.
[0072] Example 3
[0073] A method for preparing an antibacterial, mildew-resistant, and biodegradable paper box packaging material includes the following steps:
[0074] (1) Preparation of cellulose paperboard and sizing layer
[0075] 900,000 g of bleached bagasse pulp and 100,000 g of bamboo pulp were added to 49,000,000 g of deionized water to prepare 50,000,000 g of fiber pulp with a mass concentration of 2.0%. The pulp was beaten to 45°SR and then formed into paperboard. The resulting wet paperboard was pressed at 0.60 MPa for 8 minutes and dried at 95°C to a moisture content of 6.0%, with a basis weight controlled at 450 g / m². 2 Cut 1.000m 2 The cardboard is used for subsequent coating.
[0076] Add 6,000g of oxidized corn starch to 94,000g of deionized water and gelatinize at 95℃ for 25min under stirring. After cooling, add more deionized water to restore the total mass of the sizing solution to 100,000g. Apply 60,000g of the sizing solution to one side of the cardboard intended to be the inner surface of the carton and dry at 90℃ for 20min.
[0077] (2) Preparation of the five-layer antibacterial composite layer
[0078] 1.200 g of HACC was added to 80.000 g of deionized water. The HACC had a quaternary ammonium group substitution degree of 0.90 and a number-average molecular weight of 1.0 × 10⁻⁶. 5 g / mol; stir at 25℃ for 60 min, adjust pH to 6.2, and then make up to 100.000 g with deionized water to obtain a 1.2% HACC aqueous solution.
[0079] 0.600g of CMC-Na was added to 80.000g of deionized water, wherein the degree of substitution of CMC-Na was 0.90; the mixture was stirred at 25°C for 120min, the pH was adjusted to 6.2, and then deionized water was added to bring the total volume to 100.000g to obtain a CMC-Na aqueous solution with a mass concentration of 0.6%.
[0080] The coating is applied layer by layer in the following order: HACC layer, CMC-Na layer, HACC layer, CMC-Na layer, and HACC layer again. The net wet coating weight of each HACC layer is 25,000 g / m². 2 The net wet coating weight of each CMC-Na layer is 25,000 g / m². 2 After each layer is coated, it is allowed to stand for 5 minutes, and the surface liquid is removed with an air knife; the first four layers are dried at 50℃ for 6 minutes each, and the outermost layer is dried at 55℃ for 25 minutes. Based on the net wet coating weight and solution concentration, the total dry coating weight of the five antibacterial composite layers is 1.200 g / m². 2 .
[0081] (3) Preparation of β-cyclodextrin / thymol inclusion complex
[0082] 22.6996 g of anhydrous β-cyclodextrin was added to 355.6271 g of deionized water and stirred at 60 °C to dissolve, yielding a 6.0% (w / w) β-cyclodextrin aqueous solution. 3.1546 g of thymol was dissolved in 28.3916 g of 95% (v / v) ethanol to obtain a 10.0% (w / w) thymol ethanol solution; the molar ratio of β-cyclodextrin to thymol was 1:1.05.
[0083] Under stirring at 60°C, the thymol ethanol solution was added to the β-cyclodextrin aqueous solution over 20 minutes, followed by 27.89 mL of 95% ethanol. The volume was then adjusted to 500.0 mL with deionized water to achieve an ethanol volume fraction of 12.0%. The mixture was stirred at 60°C for 5 hours in a reaction vessel equipped with a reflux condenser, then cooled to 8°C and allowed to stand for 16 hours.
[0084] Prepare a 10% washing solution by diluting 6.32 mL of 95% ethanol to 60.0 mL with deionized water at 8 °C. Filter the reaction solution and wash the resulting solid twice with 60.0 mL of the washing solution. Vacuum dry the solid to constant weight under a pressure not exceeding 20 kPa and a temperature of 40 °C. Then, pulverize and classify the solid by air jet milling, collecting inclusion complexes with a particle size D90 not greater than 30 μm.
[0085] (4) Preparation of the anti-mildew layer
[0086] 1.7000g sodium alginate was slowly added to 87.9137g deionized water and stirred at 25℃ and 600r / min for 60min. Then, 0.4250g glycerol, 4.5000g of the above inclusion complex and 0.1360g calcium carbonate were added sequentially and dispersed at 800r / min for 10min. Finally, the mixture was degassed for 5min under an absolute pressure not exceeding 20kPa.
[0087] 0.5325 g of GDL was dissolved in 4.7928 g of deionized water to obtain 5.3253 g of a 10.0% GDL aqueous solution. This GDL aqueous solution was then added to the above dispersion system and mixed for 40 seconds to obtain 100.000 g of anti-mildew coating slurry. The molar ratio of GDL to calcium carbonate was 2.20:1, and the molar ratio of calcium ions to sodium alginate carboxylate ions was 0.158:1.
[0088] Within 5 minutes of adding the GDL aqueous solution, apply the anti-mildew coating slurry at a rate of 35,000 g / m². 2 The net wet coating amount is applied to the surface of the five-layer antibacterial composite layer, left to stand at 30℃ for 20 minutes, then dried at 45℃ for 40 minutes, and cooled to 35℃.
[0089] (5) Preparation of surface active layer
[0090] Add 0.2500 g of ε-poly-L-lysine hydrochloride and 0.4000 g of egg white lysozyme to 80.000 g of deionized water, stir gently at a temperature not exceeding 25°C, adjust the pH to 6.2, and then bring the total volume to 100.000 g with deionized water. No phosphate buffer or citrate buffer is added to the resulting aqueous solution. The mass ratio of ε-poly-L-lysine hydrochloride to lysozyme is 0.625:1.
[0091] The mixed aqueous solution was prepared at a concentration of 18.460 g / m³. 2 The net wet coating amount is sprayed onto the surface of the anti-mildew layer, left to stand for 10 minutes, and then dried at 35℃ for 35 minutes. Based on the coating amount and solution concentration, the total dry loading of ε-poly-L-lysine hydrochloride and lysozyme is 0.1200 g / m². 2 The obtained material was equilibrated for 24 hours at 23±2℃ and 50±5% relative humidity.
[0092] Comparative Example 1: Compared with Example 1, the preparation of the five-layer antibacterial composite layer, anti-mildew layer and surfactant layer was omitted, and only the cellulose paperboard and oxidized corn starch sizing layer were retained. The preparation conditions of the remaining paperboard were the same as those in Example 1.
[0093] Comparative Example 2: Compared with Example 1, the preparation of the anti-mildew layer and the surfactant layer was omitted. Only a five-layer antibacterial composite layer of HACC / CMC-Na / HACC / CMC-Na / HACC was prepared on the surface of the sized paperboard. The amount of other raw materials and process conditions were the same as in Example 1.
[0094] Comparative Example 3: Compared with Example 1, after the preparation of the five-layer antibacterial composite layer and the anti-mildew layer, the mixed aqueous solution containing ε-poly-L-lysine hydrochloride and egg white lysozyme was not sprayed, and the remaining raw material dosages and process conditions were the same as in Example 1.
[0095] Comparative Example 4: Compared to Example 1, the mixed aqueous solution used for the surfactant layer was replaced with a single active ingredient aqueous solution containing 0.4833 g of ε-poly-L-lysine hydrochloride and made up to 100.000 g of deionized water, at a concentration of 15.000 g / m³. 2 Spraying was performed to ensure that the total dry loading of active ingredients was the same as in Example 1, while the amounts of other raw materials and process conditions were the same as in Example 1.
[0096] Comparative Example 5: Compared to Example 1, the mixed aqueous solution used for the surfactant layer was replaced with a single active ingredient aqueous solution containing 0.4833 g of egg white lysozyme and made up to 100.000 g with deionized water, at a concentration of 15.000 g / m³. 2 Spraying was performed to ensure that the total dry loading of active ingredients was the same as in Example 1, while the amounts of other raw materials and process conditions were the same as in Example 1.
[0097] Comparative Example 6: Compared with Example 1, a mixed aqueous solution containing 0.1500% ε-poly-L-lysine hydrochloride and 0.3333% egg white lysozyme was applied to the anti-mildew coating slurry at a concentration of 15.000 g / m³ before gelation and drying. 2Spray the coating, then allow it to stand at 25°C for 10 min and dry at 35°C for 20 min. After the anti-mildew layer is dry, do not spray the mixed aqueous solution again. The amount of other raw materials and process conditions are the same as in Example 1.
[0098] Comparative Example 7: Compared with Example 1, the 3.5000g β-cyclodextrin / thymol inclusion complex in the anti-mildew coating slurry was replaced with a physical mixture formed by directly mixing 3.1091g β-cyclodextrin and 0.3909g thymol without inclusion treatment. The remaining raw material amounts and process conditions were the same as in Example 1.
[0099] Comparative Example 8: Compared to Example 1, the anti-mildew coating slurry consisted of 95.0050 g deionized water, 1.3000 g sodium alginate, 0.1950 g glycerin, and 3.5000 g inclusion complex, without the addition of calcium carbonate and GDL, at a concentration of 25.000 g / m³. 2 Spray with 1.838 g / m² after coating. 2 Anhydrous calcium chloride aqueous solution with a mass concentration of 1.0% was used, and the number of moles of calcium ions fed was the same as in Example 1. The amount of other raw materials and process conditions were the same as in Example 1.
[0100] Performance testing
[0101] 1.1 Samples were randomly cut from different locations of the paperboards obtained in Examples 1-3 and Comparative Examples 1-8, with the functional coated surface used as the test surface. Except for the microbiological test, the samples were conditioned to mass equilibrium in standard atmosphere at (23±1)℃ and (50±2)% relative humidity according to GB / T 10739—2023; the quantitative determination was performed according to GB / T 451.2—2023. Three independent parallel samples were set up for the antibacterial test, five parallel samples for Cobb60 water absorption, ten valid parallel samples for longitudinal tensile index, and three independent reactors for the biodegradation test. Except for the mildew resistance grade, the results are expressed as mean ± standard deviation. Quantitative data were analyzed using one-way ANOVA and Tukey multiple comparisons, while the mildew resistance grade was analyzed using the Kruskal-Wallis test and Dunn post-hoc comparisons. A p-value < 0.05 was considered statistically significant.
[0102] 2.1 Antibacterial properties
[0103] The antimicrobial test was performed according to Chapter 5 of GB / T 42702—2023, using the carrier antimicrobial test method. Considering the surface contact conditions of the cardboard packaging, a contact time of 120 min was selected. *Escherichia coli* (ATCC 25922) and *Staphylococcus aureus* (ATCC 6538) were used as test bacteria, and the activated bacterial solution was adjusted to 3.0 × 10⁻⁶. 5CFU / mL; Under aseptic conditions, the sample was cut into 20mm × 30mm pieces. Each portion consisted of no more than three pieces capable of completely absorbing 100μL of bacterial suspension. The functional side was placed upwards and inoculated with 100μL of bacterial suspension. The mixture was incubated at (36±1)℃ for 120 min. After incubation, 5.0 mL of phosphate buffer, verified for neutralization effectiveness, non-toxicity, and recovery effectiveness, was added. The mixture was thoroughly shaken and eluted, and then serially diluted tenfold. Two plates were inoculated for each dilution, and the plates were incubated at (36±1)℃ for 48 h before counting. Comparative Example 1 served as a control of the same material without antibacterial treatment. The initial recovered bacterial count of the control sample was controlled at 1.0 × 10⁻⁶. 4 ~5.0×10 4 CFU; the antimicrobial rate is calculated as K = (Nc - Ns) / Nc × 100%, where Nc is the average recovered number of bacteria in the control sample and Ns is the average recovered number of bacteria in the corresponding sample. Each bacterium is independently replicated three times, and the mean and standard deviation are reported. An uninoculated background control is also included. Results below the detection limit are included in the calculation according to the detection limit and are not replaced by "0 CFU".
[0104] 2.2 Resistance to mold
[0105] The determination was performed according to the petri dish method of GB / T 1741—2020. *Aspergillus niger* (CGMCC 3.5487), *Aspergillus flavus* (CGMCC 3.3950), *Cladosporium multiflorum* (CGMCC 3.2757), *Penicillium wannii* (CGMCC 3.4253), *Penicillium citrinum* (CGMCC 3.2913), and *Trichoderma viride* (CGMCC 3.2941) were activated separately, and the spore suspensions were adjusted to 1.0 × 10⁻⁶ with sterile water containing 0.05% Tween 80. 6 After mixing the samples at a concentration of 1 / mL, the samples were mixed in equal volumes. Three 50mm×50mm samples were taken from each group and cut under aseptic conditions. The samples containing lysozyme and thymol were not subjected to moist heat sterilization. The functional side of the sample was placed flat in a nutrient agar culture dish. 0.50mL of mixed spore solution was evenly inoculated into each sample and the culture medium around it. After being left to stand at room temperature for 20min, the samples were placed in an environment of (28±1)℃ and relative humidity of not less than 85% for 28d. On day 7 of incubation, it was confirmed that mold growth was observed in all three sterile filter paper positive controls and no mold growth was observed in the uninoculated background control; otherwise, the test was invalid. On day 28, visual observation was performed first. If the mold growth area was less than 10%, it was re-examined with a 50x microscope and rated as grade 0 (no growth), grade 1 (<10%), grade 2 (10% to <30%), grade 3 (30% to <60%), or grade 4 (≥60%) according to the mold growth area. The result of the sample was taken as the consistent grade of at least two samples. If any two samples differed by 2 grades or more, the test was repeated.
[0106] 2.3 Water Absorbency of Cobb 60
[0107] The water absorption of the Cobb 60 on the functional coated surface was determined according to GB / T 1540—2002. A sample was cut to cover 100cm. 2 The sample of the test ring was weighed and its mass m1 before water absorption was measured to an accuracy of 0.001 g. The test surface was then brought into contact with distilled water at (23±1)℃, with a water volume of 100 mL. The remaining water was removed after 45 s, and a quantitative amount of 200–250 g / m was applied after 60 s. 2 The sample was covered with absorbent paper, and a metal roller with a mass of (10.0±0.5) kg and a roller width of (200±0.5) mm was used to press it back and forth once within 4 seconds. The mass m2 after water absorption was immediately measured. The water absorption was calculated according to Cobb60 = (m2-m1)×100, with the unit being g / m³. 2 Five parallel samples were measured for each sample, and the mean and standard deviation were reported.
[0108] 2.4 Longitudinal Tensile Index
[0109] The tensile strength was determined according to GB / T 12914—2018 using the constant-rate tensile method. A strip specimen with a width of (15.0±0.1) mm and a length of not less than 250 mm was cut along the longitudinal direction of the cardboard. It was clamped in the tensile testing machine with a clamping distance of (180±1) mm. The clamps were adjusted so that the specimen was not under pre-tension and its long side was parallel to the direction of force. The specimen was stretched at a constant rate of 20.0 mm / min until fracture, and the maximum tensile strength F was recorded. Data from fractures at the clamping points or specimen slippage were discarded and retested. The tensile strength was calculated using S=F / w, and then... t =S / g to calculate the tensile index, where w is the sample width (m) and g is the quantitative value (g / m) measured according to GB / T 451.2—2023. 2 For each sample, 10 valid results were obtained, and the mean and standard deviation of the longitudinal tensile index were reported in N·m / g.
[0110] 2.5 Controlled compost biodegradability
[0111] The 90-day biodegradation rate was determined according to Method A of GB / T 39951—2021. The sample was cut into approximately 10mm × 10mm pieces and mixed thoroughly to prepare three 50.0g portions. A representative sample was then used to determine the total organic carbon content (A). Crude vermiculite and inoculum were mixed at a ratio of 1:3 (mass:volume) and activated at (50±2)℃ for 4 days with daily stirring. At least nine reactors with an effective volume of not less than 3L were set up, with three experimental groups, three microcrystalline cellulose reference groups, and three blank groups. Approximately 800g of activated vermiculite was added to each reactor. The experimental group received 50.0g of the sample, the reference group received approximately 50.0g of microcrystalline cellulose, and the blank group received no material. The moisture content of the mixture was adjusted to approximately 50%, and the pH to 7.0–9.0. The reactors were placed in an environment of (58±2)℃, with continuous introduction of carbon dioxide-free, water-saturated air to maintain an oxygen volume fraction in the exhaust gas of not less than 6%. The mixture was shaken weekly, and the cumulative CO2 release was continuously recorded. (D) 90 =[(TCO2-BCO2)×12] / (m×A×44)×100% to calculate the 90-day biodegradation rate, where TCO2 is the cumulative CO2 release from the experimental reactor, BCO2 is the average cumulative CO2 release from the blank reactor, and m is the sample mass. The biodegradation rate of the reference material should not be less than 70% within 45 days, and the relative deviation of the results from the three reference reactors at the test endpoint should not exceed 20%; otherwise, the test is invalid. Continue cultivation if the material has not yet reached the plateau phase after 90 days, but for a maximum of 6 months.
[0112] Table 1:
[0113] Example 1 96.4±0.6 98.0±0.4 0 41.8±1.0 48.3±0.8 90.3±0.9 Example 2 94.7±0.8 96.8±0.7 1 45.9±1.2 47.4±0.9 92.0±1.1 Example 3 97.6±0.4 98.7±0.3 0 39.6±0.8 49.1±0.7 88.9±0.8 Comparative Example 1 0.0±0.0 0.0±0.0 4 66.3±1.8 43.6±0.9 94.2±0.7 Comparative Example 2 79.8±1.8 86.7±1.4 4 58.1±1.5 47.2±0.8 92.9±0.9 Comparative Example 3 66.5±2.2 74.2±1.9 0 44.6±1.1 48.0±0.7 90.7±1.0 Comparative Example 4 87.1±1.3 91.2±1.0 0 42.4±1.1 48.0±0.8 90.5±1.0 Comparative Example 5 68.9±2.0 89.0±1.2 0 43.0±1.1 47.9±0.9 90.7±0.9 Comparative Example 6 76.4±2.1 83.5±1.7 0 44.2±1.3 47.6±0.9 90.2±1.1 Comparative Example 7 95.9±0.7 97.5±0.5 2 48.7±1.5 46.5±1.0 91.1±0.9 Comparative Example 8 93.2±1.0 95.6±0.8 1 51.9±1.6 45.8±1.1 89.6±1.1
[0114] Table 1 shows that Comparative Example 2 had antibacterial rates of 79.8% and 86.7% against *Escherichia coli* and *Staphylococcus aureus*, respectively. After forming a continuous antifungal gel layer, Comparative Example 3's rates decreased to 66.5% and 74.2%, respectively, a decrease of 13.3 and 12.5 percentage points, indicating that the outer coating layer shielded the inner contact-type cationic sites. After gelation and drying, surface loading was performed, and the two antibacterial rates of Example 1 increased to 96.4% and 98.0%, respectively, recovering 29.9 and 23.8 percentage points compared to Comparative Example 3. Comparative Example 6 only achieved 76.4% and 83.5%, indicating that post-loading helps reduce the embedding of active ingredients and maintain lysozyme activity. In Comparative Example 4, ε-polylysine had an antibacterial rate of 87.1% against *Escherichia coli*, and in Comparative Example 5, lysozyme had an antibacterial rate of 89.0% against *Staphylococcus aureus*, while Example 1 maintained a high activity against both types of bacteria. The reason for this is that ε-polylysine first binds to the anionic groups on the bacterial surface and increases membrane permeability, promoting lysozyme's approach to the peptidoglycan layer; lysozyme then hydrolyzes the β-1,4 glycosidic bonds in the peptidoglycan, causing continuous cell wall disruption and cell membrane disturbance. This result demonstrates the complementary and combined advantages of the two.
[0115] In the anti-mold results, Comparative Example 1 and Comparative Example 2 were both at level 4, indicating that without the thymol encapsulation anti-mold layer, the cardboard could not form a continuous protection in a high-humidity mold environment. After adding the β-cyclodextrin / thymol encapsulation system, Comparative Example 3, as well as Examples 1 and 3, all reached level 0, while Example 2 was at level 1. Comparative Example 7, which directly and physically mixed thymol and β-cyclodextrin, rose to level 2, indicating that free thymol volatilized rapidly during cultivation, resulting in insufficient effective concentration in the later stages. Comparative Example 8, which added calcium chloride for cross-linking, was at level 1, indicating that rapid surface gelation still provides anti-mold protection, but its network uniformity and active ingredient retention capacity are lower than those of the internal slow-release gelation system.
[0116] The water absorption capacities of Cobb60 in Examples 1, 2, and 3 were 41.8, 45.9, and 39.6 g / m³, respectively. 2 All were lower than the 66.3 g / m² of Comparative Example 1. 2 This indicates that multilayer deposition and alginate gel can fill the pores on the cardboard surface and reduce short-term water absorption; Comparative Examples 7 and 8 increased to 48.7 and 51.9 g / m, respectively. 2 This further reflects the influence of inclusion state and gel uniformity on coating continuity. The longitudinal tensile indices of the three examples were 48.3, 47.4, and 49.1 N·m / g, respectively, which were higher than 43.6 N·m / g of Comparative Example 1, and no significant strength loss was observed due to functionalization treatment. The 90-day biodegradability rates of the three examples were 90.3%, 92.0%, and 88.9%, respectively, which were on a similar order of magnitude to 94.2% of Comparative Example 1, indicating that the low coating amount of natural polysaccharide functional layer only had a limited impact on the decomposition rate, and the material still maintained the biodegradability characteristics mainly composed of plant fibers and biodegradable polysaccharides.
[0117] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the essence and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing an antibacterial, mildew-resistant, and biodegradable paper box packaging material, characterized in that, Includes the following steps: (1) Provide cellulose paperboard; (2) On at least one side surface of the cellulose paperboard, water-soluble 2-hydroxypropyltrimethylammonium chloride chitosan aqueous solution and carboxymethyl cellulose sodium aqueous solution are prepared separately and coated layer by layer, and each layer is dried after coating to form a five-layer antibacterial composite layer consisting of a 2-hydroxypropyltrimethylammonium chloride chitosan layer, a carboxymethyl cellulose sodium layer, a 2-hydroxypropyltrimethylammonium chloride chitosan layer, a carboxymethyl cellulose sodium layer and a 2-hydroxypropyltrimethylammonium chloride chitosan layer from the cellulose paperboard outwards; (3) The inclusion complex formed by β-cyclodextrin and thymol is dispersed in an aqueous coating system containing sodium alginate and calcium carbonate. Finally, gluconate-δ-lactone is added, and the resulting coating slurry is coated on the five-layer antibacterial composite layer before gelation is completed, so that the calcium ions released by calcium carbonate crosslink sodium alginate in situ, and an anti-mildew layer is formed after gelation and drying. (4) After the anti-mildew layer has completed gelation, drying and cooling, a mixed aqueous solution containing ε-poly-L-lysine and lysozyme is applied to the surface of the anti-mildew layer away from the cellulose paperboard and dried to obtain the antibacterial and anti-mildew biodegradable paper box packaging material.
2. The preparation method according to claim 1, characterized in that, The method for preparing the cellulose paperboard is as follows: Based on a total of 100 parts by weight of oven-dry pulp, 75-90 parts of bleached bagasse pulp and 10-25 parts of bamboo pulp are mixed, totaling 100 parts; water is added to prepare a fiber pulp with a mass concentration of 1.0%-2.0%, and the pulp is beaten to 35-45°SR and then formed into a wet paper sheet; the wet paper sheet is pressed at 0.3-0.6 MPa for 3-8 minutes and dried at 80-95°C to a moisture content of 6%-9%, yielding a basis weight of 300-450 g / m³. 2 Cellulose paperboard.
3. The preparation method according to claim 1, characterized in that, Before forming the five-layer antibacterial composite layer, the cellulose paperboard is surface-sized. The surface sizing includes: preparing an aqueous dispersion of oxidized corn starch with a mass concentration of 4% to 6%, gelatinizing it at 85 to 95°C for 15 to 25 minutes, and applying it at a concentration of 40 to 60 g / m³. 2 A wet coating is applied to the surface of the cellulose paperboard and dried at 80-90°C to form an oxidized corn starch sizing layer; the five-layer antibacterial composite layer is formed on the oxidized corn starch sizing layer.
4. The preparation method according to claim 1, characterized in that, The quaternary ammonium group substitution degree of the 2-hydroxypropyltrimethylammonium chloride chitosan is 0.70–0.90, and the number average molecular weight is 5.0 × 10⁻⁶. 4 ~1.0×10 5 g / mol; the degree of substitution of the sodium carboxymethyl cellulose is 0.70–0.90; the mass concentration of the 2-hydroxypropyltrimethylammonium chloride chitosan aqueous solution is 0.8%–1.2%, the mass concentration of the sodium carboxymethyl cellulose aqueous solution is 0.4%–0.6%, and the pH of the two aqueous solutions is 5.8–6.2; the wet coating amount of each layer of 2-hydroxypropyltrimethylammonium chloride chitosan is 15–25 g / m². 2 The wet coating weight of each layer of sodium carboxymethyl cellulose is 18–28 g / m². 2 After each layer is coated, allow it to stand for 2–5 minutes, then remove excess liquid from the surface using an air knife. Dry each layer except the outermost layer at 40–50°C for 3–6 minutes, and dry the outermost layer at 45–55°C for 15–25 minutes. The total dry coating weight of the five antibacterial composite layers is 0.5–1.2 g / m². 2 .
5. The preparation method according to claim 1, characterized in that, The inclusion complex is prepared as follows: β-cyclodextrin is dissolved in water at 50–60°C to prepare a β-cyclodextrin aqueous solution with a mass concentration of 4%–6%; thymol is dissolved in ethanol with a volume fraction of 95% to prepare a thymol ethanol solution with a mass concentration of 5%–10%; the thymol ethanol solution is added to the β-cyclodextrin aqueous solution within 10–20 min at a molar ratio of 1:0.95–1.05 between β-cyclodextrin and thymol, so that the volume fraction of ethanol in the resulting mixture is 8%–12%; the mixture is stirred at 50–60°C for 3–5 h in a reaction vessel equipped with a reflux condenser, then cooled to 2–8°C and allowed to stand for 8–16 h, filtered, and the resulting solid is washed with an ethanol aqueous solution with a volume fraction of 10% at 2–8°C, and then vacuum dried at 35–40°C to obtain an inclusion complex with a particle size D90 of no more than 30 μm.
6. The preparation method according to claim 1, characterized in that, Based on the total mass of the coating slurry obtained after adding glucono-δ-lactone, the coating slurry contains 1.3% to 1.7% sodium alginate, 3.5% to 4.5% inclusion complex, 15% to 25% glycerol, and 5% to 8% calcium carbonate. The coating slurry is prepared by mixing and dispersing sodium alginate aqueous solution, glycerol, inclusion complex, and calcium carbonate, degassing, and finally adding glucono-δ-lactone aqueous solution.
7. The preparation method according to claim 6, characterized in that, The molar ratio of gluconate-δ-lactone to calcium carbonate is 2.0–2.2:1; calculated based on the complete release of calcium ions from calcium carbonate, the molar ratio of calcium ions to carboxylate ions in sodium alginate is 0.10–0.16:1; after adding the gluconate-δ-lactone aqueous solution, mix for 20–40 seconds, and then increase the concentration by 25–35 g / m³ within 5 minutes. 2 After applying the wet coating, let it stand at 25-30℃ for 10-20 minutes, and then dry it at 35-45℃ for 20-40 minutes.
8. The preparation method according to claim 1, characterized in that, The ε-poly-L-lysine is ε-poly-L-lysine hydrochloride, and the lysozyme is egg white lysozyme; the mixed aqueous solution uses deionized water as a solvent, wherein the mass concentration of ε-poly-L-lysine hydrochloride is 0.15%–0.25%, the mass concentration of lysozyme is 0.25%–0.40%, the mass ratio of ε-poly-L-lysine hydrochloride to lysozyme is 0.45–0.75:1, the pH of the mixed aqueous solution is 5.8–6.2, and it does not contain phosphate buffer or citrate buffer.
9. The preparation method according to claim 8, characterized in that, After cooling the anti-mildew layer to no higher than 35°C, apply 15-25 g / m³. 2 The mixed aqueous solution is sprayed with a wet spray amount, allowed to stand for 5-10 minutes, and then dried at 30-35°C to achieve a total dry loading of 0.07-0.12 g / m³ for ε-poly-L-lysine hydrochloride and lysozyme. 2 .
10. An antibacterial, mildew-resistant, and biodegradable paper box packaging material, characterized in that, It is prepared by the method described in any one of claims 1 to 9 above.